Light-cured resin "Barricaid" - An aesthetic and biocompatible dressing: A step ahead - Ellora Madan; Vipin Bharti; K K Chaubey; Vipin K. R. Arora; Rajesh K Thakur; Anubha Nirwal (Wolters Kluwer Medknow Publications, 2013)
Background: Periodontal dressings have been used for several years as a protection over injured tissue to shield the area from further insult . Several dressings are commercially available. A recently introduced light-cured resin, claimed to be more biocompatible and esthetic, needs critical evaluation. Aim: To compare this dressing with most widely used non-eugenol pack in the perspective of esthetics, acceptance, and healing following periodontal flap surgery. Materials and Methods: Twenty patients suffering from generalized chronic periodontitis, requiring periodontal flap surgery on contralateral sides of the arch, were selected and divided randomly into Group I (control) and Group II (test). In Group I, a non-eugenol dressing and in Group II light-cured dressing were applied after flap surgery. Pain and discomfort scores were recorded on day 1, 2, and 3 while plaque scores, gingival index, and bleeding index were recorded on day 7. Patient's subjective evaluation and preference for the dressing material were recorded. The data was collected and statistically analyzed. Results: Group II showed better results than Group I when plaque scores, bleeding scores, modified gingival index scores, and pain and discomfort scores were compared though the differences were not statistically significant. Subjects found no unpleasant taste/smell and perceived the light-cured dressing to be better. A significantly higher number of patients preferred light-cured resin as a post-surgical dressing over Coe-pak. Conclusion: The light-cured dressing showed better patient acceptability and proves to be a better alternative to Coe-pak as a dressing material.